Ángel Ferrant. La renovación de la enseñanza artística - Asenjo Fernández, Ignacio (Arte, Individuo y Sociedad, 2007)
The teaching aspect of the sculptor Ángel Ferrant career has been fatally ignored, even if he has taught in various Arts & Crafts Schools during four decades. He was a cultivated man, concerned by art teaching and its renovation. He wrote several works on pedagogic reform, and was also interested in children's art, publishing articles on the subject. Furthermore, Ferrant filed a valuable and extensive personal documentation about his didactic work: didactic texts, letters, publications, school photographs, quotations, notes, etc., which are at the base of this work. Necessarily, his memory must be recovered.